Revolutionizing Elementary Math Learning: Exploring the Potential of Metaverse Technology Integration - Loso Judijanto; Guntur Arie Wibowo; Syamsul Ghufron; Nunung Suryana Jamin; Abdul Rozak (Universitas Pendidikan Ganesha, 2024)
The integration of metaverse technology in education continues to evolve, providing immersive learning experiences. However, its implementation in elementary mathematics education remains limited, resulting in low student engagement. This study aims to analyze the extent to which teachers utilize metaverse technology in teaching mathematics at the elementary level. Employing a quantitative approach, data were collected using questionnaires administered to teachers and gifted student supervisors. The findings reveal that teachers significantly recognize and utilize metaverse technology in mathematics instruction, positively influencing student engagement and creating more meaningful learning experiences. The perspectives of teachers and supervisors indicate that integrating metaverse technology supports more effective teaching practices. The data analysis shows a statistically significant difference between teachers’ and supervisors’ perspectives regarding the use of metaverse technology, particularly among individuals who have attended more than two related training sessions. However, no significant differences were found based on teaching experience with gifted students. This study concludes that metaverse technology holds great potential for integration into elementary mathematics education, promoting sustainable educational innovation. It can enhance students' interest and understanding of mathematical concepts through interactive and engaging learning environments.